2021
DOI: 10.3390/antiox10122023
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Carotenoids, Polyphenols, and Estradiol on Dermal Fibroblasts under Oxidative Stress

Abstract: Skin ageing is influenced by several factors including environmental exposure and hormonal changes. Reactive oxygen species (ROS), which mediate many of the effects of these factors, induce inflammatory processes in the skin and increase the production of matrix metalloproteinases (MMPs) in dermal fibroblasts, which leads to collagen degradation. Several studies have shown the protective role of estrogens and a diet rich in fruits and vegetables on skin physiology. Previous studies have shown that dietary caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 63 publications
0
11
0
3
Order By: Relevance
“…Such effects were reversed by the daily consumption of sweet pepper juices. A recent study has shown that carotenoids- and polyphenol-rich extracts reduced MMP-1 expression and simultaneously enhanced procollagen synthesis in normal human dermal fibroblasts under the condition of oxidative stress [ 40 ]. Although both HSB and LSM juices did not reduce MMP-2 expression and LSM juice was more effective in reducing MMP-9 expression, in general, the efficacy of HSB and LSM juices was similar and comparable to that of positive control vitamin C. These findings suggest that sweet pepper juice exerts anti-photoaging activity in a model of UVB-irradiated hairless mice by increasing collagen synthesis and suppressing collagen degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Such effects were reversed by the daily consumption of sweet pepper juices. A recent study has shown that carotenoids- and polyphenol-rich extracts reduced MMP-1 expression and simultaneously enhanced procollagen synthesis in normal human dermal fibroblasts under the condition of oxidative stress [ 40 ]. Although both HSB and LSM juices did not reduce MMP-2 expression and LSM juice was more effective in reducing MMP-9 expression, in general, the efficacy of HSB and LSM juices was similar and comparable to that of positive control vitamin C. These findings suggest that sweet pepper juice exerts anti-photoaging activity in a model of UVB-irradiated hairless mice by increasing collagen synthesis and suppressing collagen degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary carotenoids combined with rosemary extract containing carnosic acid having abilities to activate Nrf2/ARE system exerted an inhibitory effect on UVB (20–60 mJ/cm 2 )-induced TNF-α and MMP-1 secretion from dermal fibroblasts ( Calniquer et al, 2021 ). The tomato extracts rich in lycopene also protected against H 2 O 2 -induced photodamage of fibroblasts via promotion of pro-collagen secretion and suppression of apoptotic cell death and ROS formation ( Darawsha et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Novel active ingredients are required to retard or prevent skin aging by suppressing the harmful effects of UV. Especially, many researchers have demonstrated that natural polyphenols worldwide can be identified as a potential active ingredient to improve the aged skin dermis [ 10 , 11 , 12 ]. Polyphenol is a type of aromatic alcohol compound found in plants and is characterized by having several hydroxyl groups with a functional group of two or more phenyl groups [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%